STRATEGIC BARRIERS TO GREEN INNOVATION ADOPTION IN MINING ENTERPRISES OF RESOURCE-BASED ECONOMIES - Kurbanova Mehriniso Nematjanovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This thesis examines strategic barriers to green innovation adoption in mining enterprises of resource-based economies. The study focuses on the mining sector as a resource-intensive industry where environmental modernization is economically necessary but institutionally and technologically difficult to implement. Using the case logic of a large gold mining and metallurgical enterprise, the thesis identifies five major groups of barriers: capital intensity, technological inertia, energy and water dependence, organizational fragmentation, and delayed financial return. The findings suggest that green innovation adoption requires not only new equipment but also coordinated project management, digital monitoring, ESG-oriented governance and long-term investment planning.